The Effect Of Using The Fishbowl Strategy Toward Students' Speaking Ability - Sari, Meliya; Sujarwati, Iis (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
The Fishbowl teaching strategy has been investigated for its impact on enhancing students' speaking proficiency in secondary education. Despite regular engagement in English through day-to-day interactions, students often find English instruction monotonous and uninspired, primarily due to the reliance on traditional pedagogical approaches. In response, this study aimed to collect empirical data on the efficacy of the Fishbowl strategy in a classroom setting. Utilizing a quasi-experimental design, the research population comprised second-grade students from SMAN 06 Bengkulu Utara, focusing specifically on their speaking abilities as influenced by the Fishbowl method. The sample population consisted of 68 students, classified into two distinct groups: the experimental group, which experienced the Fishbowl intervention, and the control group, which did not. A comparative analysis of average pre-test and post-test speaking scores was conducted using SPSS software to assess the intervention's effectiveness. The statistical significance of the results was evaluated with the t-test formula. Findings indicated a significant difference in speaking abilities between students instructed through the Fishbowl strategy and those in the control group, with the experimental group achieving a t-test score of 70.00, demonstrating pronounced improvements in their speaking competencies. The implementation of the Fishbowl strategy was noted to be not only compelling but also inspiring, fostering a more engaging and productive learning environment.